Um olhar preventivo ao distúrbio de ansiedade e a dificuldade no aprendizado - Noronha, Erivelton Carvalho (Brasil, 2021)
Mental health has been increasingly the subject of interest in works, research and scientific articles in various areas, ranging from health to the field of education. Studies show that since 2017, Brazil has had the largest number of people with anxiety disorders in the world. There are almost 19 million Brazilians with their quality of life compromised by this disorder. In addition, the Covid-19 pandemic caused by Coronavirus contributed directly, triggering mental disorders and even aggravating existing cases. This disorder, in turn, directly interferes with student learning, hindering the ability to acquire knowledge, retain or use skills and abilities, which affects academic performance. Given this reality, the aim of this article was to prepare an informative booklet focused on the reality of the city of Coari - Amazonas, providing a tool and indicating the possibility of helping these cases in our school environment. Thus, the booklet was built using the Powerpoint application according to the recommendations for the design and effectiveness of educational materials, according to the characteristics of the content, language, organization, layout, illustrations and information, keeping in mind two basic principles, that of promoting self-information and help in seeking appropriate help. It was verified the importance of an informative material capable of contributing to change the reality of our students.